Functions of administrative law: historical and legal aspect - Миронець, Оксана Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
In the article the historical and legal aspects of functions of administrative law have been investigated. The periodization of the formation of the administrative law functions has been made by the author. The point of view that their understanding dependes on the scientific vision of a subject of administrative law has been proved.